TRENDS IN PRE-SERVICE PRIMARY SCHOOL TEACHERS’ ADMISSION TO HIGHER EDUCATIONAL INSTITUTIONS IN THE BENELUX COUNTRIES - Holovatenko, Tetiana (The Modern Higher Education Review, 2022)
This article is a comparative research on the admission process to higher educational institutions in the Benelux countries. In this paper, the author aimed at identifying trends in the admission process to the Primary Education programs in the Benelux countries and ways to implement best practices into Ukrainian realities. The study is grounded in a qualitative methodology, with a wide range of empirical methods used. Collected data is structured on organizational, content and assessment levels of trends. On the organizational level, we have identified trends in the digitalization of the admission process to teaching programs; commercialization of the admission process; organization of a multistep enrolment procedure. On the content level, we have identified trends in the identification of compulsory subject tests for applicants; including the identification of motivation and personal aptitude towards teaching into the admission process. On the assessment level, we identified trends in taking the results of the admission test as a formative assessment. The article addresses various ways to implement best practices in Ukraine.